Expatriates and International career management: Corporate and sporting context - Wallan-Tertuliano Ivan; de Oliveira Vivian; Alves-Santana Bruna (Ekonomski Pogledi, 2019)
Globalization makes expatriation an increasingly present reality, whether in the lives of employees of multinational companies or athletes. Therefore, the objective of this essay was to conceptuate the International Human Resources Management (IHRM) and to point out the relationship of such phenomenon with the career management conducted by the person participating in this process of "expatriation", both in corporate and sports contexts. For this, it was based on the methodological design of a qualitative research on the perspective of documental analysis. As the main reflections of this essay, we emphasize that, although it is considered fundamental, the IHRM is better developed in companies, while in sports clubs this is a secondary concern. It is also noteworthy the importance of athletes and expatriate employees to undergo a process of preparation, both from the psychological and social, economic and cultural point of view, so that the changes are faced in the best possible way.